Strategic development framework for the army officers' on-base housing a model development for the Philippine Army Housing Community - Sy, Juanito Y. (College of Architecture, University of the Philippines Diliman, 2008)
This study aimed to develop a strategic framework for the development of on-base housing facilities for the officers of the Philippine Army through a post-occupancy evaluation of existing housing units in both urban and rural camps. Results of the survey were augmented by findings from two (2) fronts : a present-conditions where the units are located, and documentary and structural analysis of the organization and policies of the housing administrative bodies of the Armed Forces of the Philippines and the Philippine Army in particular. This study was guided by two housing research and design models. The first is proposed by Jim Kemeny which suggests that housing research should be conducted within a framework that considers various components such as the inhabitants, the physical aspects, the neighborhood, and the social structure are equally relevant and interrelated to one another for policy makers to craft guidelines that result in residential communities that truly serve the needs of the inhabitants of the community. The second model is Elizabeth Wood's Social Theory of Housing Design which "propounds the theory that the rich fulfillment of the needs of people, as individuals and groups, is in itself a suitable objective." The approach of this study therefore embraces the philosophy that dwelling units and neighborhood environments must be responsive to the needs and desires of the user as well as strike a balance between quality dwelling design on one hand and resources constraints on the other. The output of the study is a strategic development approach that hinges on two (2) major frameworks : the Community and Administrator Reform Environment "CARE" Framework", otherwise known as the soft approach, which deals with the proposed organization and improvement of the mission and functions of the sectors involved in the delivery of workable and attractive housing neighborhoods, and the Socio-Physical Adaptability and Cultural Environment of SPACE Framework", the hard approach, which deals with the physical aspect of housing and community development.